A produção das fricativas alveolares do inglês por aprendizes brasileiros: uma análise acústica sob a perspectiva do inglês como língua franca - Oliveira, Gisele Paixão de (2014)
This research aims to describe and analyze the fricatives [s] and [z] in coda position as well as the duration of the previous vowels. Based on that, fifteen participants in three different proficiency levels (basic, intermediate and advanced) who had the production of twelve monosyllabic minimal pairs inserted in vehicle sentences were recorded. The data were submitted to acoustic and statistical analysis and the objective was to verify if the participants transferred the mother language pronunciation patterns to the target language or if they made use of the English pronunciation rules. The results were analyzed under the perspective of the Usage-based Phonology (Bybee, 2001) and English as a Lingua Franca (Jenkins, 2000; 2007).